Positive Clinical Psychology and Schema Therapy (ST): the development of the Young Positive Schema Questionnaire (YPSQ) to complement the Young Schema Questionnaire 3 Short Form (YSQ-S3) - Louis, John P.; Wood, Alex M.; Lockwood, George; Ho, Moon-Ho Ringo; Ferguson, Eamonn (American Psychological Association, 2018)
Negative schemas have been widely recognized as being linked to psychopathology and mental health, and they are central to the Schema Therapy (ST) model. This study is the first to report on the psychometric properties of the Young Positive Schema Questionnaire (YPSQ). In a combined community sample (Manila, Philippines, n = 559; Bangalore, India, n = 350; Singapore, n = 628), we identified a 56-item 14-factor solution for the YPSQ. Confirmatory factor analysis supported the 14-factor model for data from the Singapore sample as well as 2 other samples; an Eastern sample from Kuala Lumpur, Malaysia (n =229) and a Western sample from the United States (n = 214). Construct validity was demonstrated with the Young Schema Questionnaire 3 Short Form (YSQ-S3) that measures negative schemas and divergent validity was demonstrated for 11 of the YPSQ subscales with their respective negative schema counterparts. Convergent validity of the 14 subscales of YPSQ was demonstrated with measures of personality dispositions, emotional distress, well-being, trait gratitude, and humor styles. Positive schemas also showed incremental validity over and above negative schemas for these same measures thus demonstrating that both positive and negative schemas are separate constructs that relate in unique ways to mental health. Implications for using both the YPSQ and the YSQ-S3 scales in tandem in ST as well as cultural nuances from the use of Asian samples were discussed.